EVALUASI DESAIN RANCANG BANGUN PUNCH DAN DIE MENGGUNAKAN SIMULASI STATIK SEBAGAI QUALITY CONFIRMATION - Edwin Sahrial Solih; Ahmad Arif; Sanurya Putri Purbaningrum; Desy Agustin; Abdul Wahid Arohman; Fadhil Fadhlurrohman Nurhadi; Fredy Sumasto (Scientific Journal of Mechanical Engineering Kinematika, 2025)
Modern manufacturing industries demand high efficiency and consistent product quality, especially in metal forming processes such as stamping dies. An accurate punch and die design essential to ensure the success of bending operations, particularly for metal-based products like forks. This study aims to evaluate the structural reliability of punch and die designs through a static simulation approach as a quality confirmation method prior to manufacturing. The methodology includes die geometry design, selection of SKD11 tool steel based on its mechanical properties, and stress analysis using SolidWorks software under a static load of 35 tons. The stress distribution was analyzed using the Von Mises method, and the Factor of Safety (FOS) was calculated as a design safety indicator. Simulation results show that the maximum stress on the die was 9.91 × 10⁷ N/m² and on the punch was 1.01 × 10⁸ N/m², both well below the yield strength of SKD11 (6.88 × 10⁸ N/m²). The FOS values of 3.47 for the die and 3.26 for the punch confirm structural safety. Validation through trial dies and 3D scanner measurements indicated dimensional deviations within the acceptable tolerance range. This approach effective for improving design accuracy and production efficiency in stamping die manufacturing.